BEHAVIORAL BARRIERS IN THE PROCESS OF MAKING PURCHASE DECISIONS (Marketing Journal, 2025)
This study examined key behavioral barriers in consumer decision -making. Emotional distortions, information overload, and cognitive shortcuts were identified as significant factors affecting purchase frequency and cost evaluation. Using regression 611 and correlation analysis, a weak link was found between rational assessment and actual consumer behavior. Emotional responses were shown to exert consistent influence on decisions even under high information exposure. It was concluded that incorporating behavioral variables into forecasting models and policy design enhances the understanding of consumer behavior in complex retail environments.
Keywords: consumer behavior; emotional bias; information overload; cognitive barriers; rational choice; behavioral economics